Quando Argenta era un castello - Benedetta Bolognesi (Annali Online dell'Università di Ferrara. Sezione Lettere)
The paper focuses on the walls of Argenta from the 12th till 18th century, showing how the evolution of the city’s walls is a means of retracing the history of the city.